Low Level of CD4 Increases Risk of Cervical Intraepithelial Neoplasia in HIV-Infected Women - Mariana, Mona (Indonesian Socety of Obstetrics and Gynecology, 2014)
Objective: To study the risk of Cervical Intraepithelial Neoplasia (CIN) at higher CD4 levels compared to low CD4 levels in HIV-infected women. Method: Case-control study of 50 HIV-infected women who meet the inclusion and exclusion criteria and attended Kerti Praja Foundation outpatient clinic, Denpasar, who were then divided into 2 groups, those with CD4 500/mm3 and those with CD4